Arginase 1 contributes to diminished coronary arteriolar dilation in patients with diabetes. - Beleznai, T; Feher, A; Spielvogel, D; Lansman, S; Bagi, Z (2011)
Arginase 1, via competing with nitric oxide (NO) synthase for the substrate L-arginine, may interfere with NO-mediated vascular responses. We tested the hypothesis that arginase 1 contributes to coronary vasomotor dysfunction in patients with diabetes mellitus (DM). Coronary arterioles were dissected from the right atrial appendages of 41 consecutive patients with or without DM (the 2 groups suffered from similar comorbidities), and agonist-induced changes in diameter were measured with videomicroscopy. We found that the endothelium-dependent agonist ACh elicited a diminished vasodilation and caused constriction to the highest ACh concentration (0.1 μM) with a similar magnitude in patients with (18 ± 8%) and without (17 ± 9%) DM. Responses to ACh were not significantly affected by the inhibition of NO synthesis with N(G)-nitro-L-arginine methyl ester in either group. The NO donor sodium nitroprusside-dependent dilations were not different in patients with or without DM. Interestingly, we found that the presence of N(G)-hydroxy-L-arginine (10 μM), a selective inhibitor of arginase or application of L-arginine (3 mM), restored ACh-induced coronary dilations only in patients with DM (to 47 ± 6% and to 40 ± 19%, respectively) but not in subjects without DM. Correspondingly, the protein expression of arginase 1 was increased in coronary arterioles of patients with DM compared with subjects without diabetes. Moreover, using immunocytochemistry, we detected an abundant immunostaining of arginase 1 in coronary endothelial cells of patients with DM, which was colocalized with NO synthase. Collectively, we provided evidence for a distinct upregulation of arginase 1 in coronary arterioles of patients with DM, which contributes to a reduced NO production and consequently diminished vasodilation.